2018
DOI: 10.1093/infdis/jiy368
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of Longitudinal Preexposure Prophylaxis Adherence Among Men Who Have Sex With Men

Abstract: Background. Adherence is necessary for efficacy of preexposure prophylaxis (PrEP), and text-messaging methods are promising tools for both adherence assessment and support. Although PrEP adherence is variable, little research has examined patterns of variability or factors associated with longitudinal use.Methods. In the context of a randomized controlled trial of text-messaging versus standard of care for PrEP adherence, 181 men who have sex with men received once-daily tenofovir disoproxil fumarate/emtricita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
2
38
1
1
Order By: Relevance
“…Overall, 63% of participants had TFV‐DP DBS concentrations correlating to four or more doses per week at all visits, and only 2.9% consistently had concentrations correlating to less than two doses per week. Other ongoing demonstration projects and refill data have identified predictors of adherence to PrEP to include age, race, sex, substance use, comorbidities, risk behavior, and partnership type . Overall, the adherence monitoring done in these studies indicate that adherence is better during times of higher perceived risk, although the large demonstration projects have found that, on average, adherence to PrEP wanes over time.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, 63% of participants had TFV‐DP DBS concentrations correlating to four or more doses per week at all visits, and only 2.9% consistently had concentrations correlating to less than two doses per week. Other ongoing demonstration projects and refill data have identified predictors of adherence to PrEP to include age, race, sex, substance use, comorbidities, risk behavior, and partnership type . Overall, the adherence monitoring done in these studies indicate that adherence is better during times of higher perceived risk, although the large demonstration projects have found that, on average, adherence to PrEP wanes over time.…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][11][12][13][14][15] Although self-reported adherence measures seem to overestimate actual adherence, 16 trials measuring TFV-DP drug levels reported adequate adherence (corresponding to 4 or more tablets a week) in about 80%-90% of study participants, whereas near-perfect adherence (corresponding to 7 or more tablets a week) in 40%-50% of study participants. 17,18 However, these published data do not inform us about PrEP use and adherence after roll-off from PrEP trials and PrEP demonstration projects, when participants are challenged with establishing care, acquiring PrEP, and remaining adherent. 14,[19][20][21][22] This study aimed to identify predictors of the PrEP adherence posttrial period for participants completing the TAPIR randomized controlled trial of text messaging versus standard care for adherence to daily TDF/FTC PrEP in MSM in Southern California between 2014 and 2016 (NCT01761643).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, participants at visits with suboptimal and WCD concentrations were more likely to report not consistently discussing HIV serostatus before intercourse, compared with visits with optimal drug concentrations. This observation is particularly notable, as these risk behaviors occurred in the context of inadequate prevention-effective drug concentrations, potentially leaving participants vulnerable to HIV acquisition, underscoring the importance of barriers that may impede PrEP adherence in spite of sexual risk behavior [ 16–19 ]. Furthermore, these findings highlight the need for increased attention to identifying and reducing these barriers, particularly as HIV acquisition in the setting of inadequate prevention-effective drug concentrations may select for resistant viral quasispecies should seroconversion occur [ 20 ].…”
Section: Discussionmentioning
confidence: 99%